PREMESSE PER UN APPROCCIO LINGUISTICO AL TESTO DELLA SACRA SCRITTURA. LE VALENZE DEL LINGUAGGIO DELLA FEDE VISTO COME ATTO CREATORE - BENCE-MUK, Mirona (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2017)
Premises for a Linguistic Approach of the Text of the Sacred Writings Virtues of the Language of Faith as Act of Creation. The present article aims to certify the validity of the assumptions launched by the philosophy of language, as it has been theorized over the centuries by Aristotle, Humboldt, Hegel and, later on, by Eugeniu Coseriu, using the text of the Holy Bible as demonstrative and applicative support. Through his theories in regard to language, more precisely in regard to the creative nature of language, Coseriu recognizes the tridimensionality of the word (ἐνέργεια- enérgeia, δύναμις-dynamis, ἔργον-ergon), previously stated by Aristotle. He thus leads the way towards possible nuances by means of particular employment of the above mentioned tridimensionality. We resort to the text of the Sacred Writ given the fact that it proves itself to be the foremost source in demonstrating what Aristotle names the mood of potentiality and of actuality of the human being by the power of language. Premise pentru o abordare lingvistică a textului Sfintei Scripturi. Valenţele limbajului credinţei ca act creator. Articolul de faţă îşi propune să certifice validitatea premiselor lansate de filosofia limbajului, aşa cum a fost ea teoretizată de-a lungul timpului de Aristotel, Humboldt, Hegel și, ulterior, de Eugeniu Coşeriu, utilizând ca suport demonstrativ şi aplicativ textul biblic. Prin intermediul tezelor sale integraliste cu privire la limbaj, respectiv la natura creativă a limbajului, Coşeriu recunoaşte tridimensionalitatea cuvântului (ἐνέργεια- enérgeia, δύναμις-dynamis, ἔργον-ergon), afirmată în prealabil de Aristotel, şi ne deschide calea spre posibile nuanţări, prin intermediul unor aplicaţii inedite ale acesteia. Vom recurge la textul Sfintei Scripturi deoarece se dovedeşte a fi sursa primordială în demonstrarea a ceea ce Aristotel numeşte modul de a-fi-în-potenţă şi de a-fi-ca-act al fiinţei, prin forţa limbajului. Cuvinte-cheie: ἐνέργεια-enérgeia, δύναμις-dynamis, cuvânt, limbaj, discurs, lingvistică integrală, mister, «universul de discurs al credinţei», act creator, «Verbum».